IbM pelatihan supervisi akademik bagi guru di Kabupaten Majene Sulawesi Barat - Ismail Tolla; Ratmawati Ratmawati (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The general objective of this activity is to improve the fulfillment of teacher competency needs in the implementationof supervision starting from the preparation, implementation, results and follow-up to the implementation of supervision that isdirectly related to improving the quality of learning in schools. The target of community service activities is to make a realcontribution to partners in meeting the need to improve teacher competency in conducting academic supervision, so that teachersare more professional in the learning process activities at school. The method used to improve the professional competence ofteachers in improving the quality of the learning process is to conduct academic supervision training for teachers in MajeneRegency, West Sulawesi Province. The implementation of the service program has been carried out for two days in the QualityAssurance Hall of West Sulawesi. The outcomes of teachers participating in this training are: (1) gaining better insights aboutthe concepts and implementation of academic supervision (2) gaining insight into techniques and procedures implementation ofsupervision and (3) gaining insight into strategies in preparing, implementing and following up on academic supervision resultsand (4) having better skills in preparing, implementing and coordinating the results of academic supervision to improve andmaximise the quality of learning.